Bioelectrical impedance vector analysis-derived phase angle predicts survival in patients with systemic immunoglobulin light-chain amyloidosis. (2nd July 2020) - Caccialanza, Riccardo; Cereda, Emanuele; Klersy, Catherine; Milani, Paolo; Cappello, Silvia; Martinelli, Valentina; Turri, Annalisa; Basset, Marco; Borioli, Valeria; Nuvolone, Mario; Caraccia, Marilisa; Lavatelli, Francesca; et al.
Abstract: Background: The aim of the present prospective study (ClinicalTrials.gov Identifier: NCT02111538) was to assess the prognostic value of phase angle (PhA), derived from bioimpedance vectorial analysis (BIVA), in patients affected by systemic amyloid light-chain (AL) amyloidosis. Methods: One hundred-twenty seven consecutive newly diagnosed, treatment-naïve patients with histologically confirmed AL amyloidosis were enrolled. Nutritional assessment including BIVA-derived PhA was performed before treatment initiation. Results: PhA was associated with unintentional weight loss, caloric intake and the physical component of quality of life (QoL). After a median follow-up of 16.3 months (25th–75th percentile: 8.4–28.9 months), 49 (38.6%) subjects had died. At multivariable Cox proportional hazard analysis, PhA ≤4.3 independently predicted survival (HR = 2.26 [95%CI, 1.04–4.89]; p = .038]) after controlling for hydration status, haematologic response to treatment and modified Mayo Clinic cardiac stage. There was no effect modification of PhA on mortality by cardiac stage (P for interaction = 0.61). Conclusions: In AL amyloidosis, BIVA-derived PhA is associated with the common parameters implied in malnutrition assessment and QoL, and adjusted for hydration independently predicts survival. Due to its feasibility, BIVA should be systematically considered for the nutritional and clinical assessment of AL patients, in whom nutritional intervention trials are warranted.